2021
DOI: 10.3390/ijms22052487
|View full text |Cite
|
Sign up to set email alerts
|

OsCBE1, a Substrate Receptor of Cullin4-Based E3 Ubiquitin Ligase, Functions as a Regulator of Abiotic Stress Response and Productivity in Rice

Abstract: Ubiquitination is an important environmental stress response, and E3 ubiquitin ligases play a major role in the process. T-DNA insertion mutants of rice, Oscbe1-1, and Oscbe1-2, were identified through the screening of cold stress tolerance at seedling stage. Oscbe1 mutants showed a significantly higher cold stress tolerance in the fresh weight, chlorophyll content, and photosynthetic efficiency than wild type. Molecular prediction showed that OsCBE1 (Oryza sativa Cullin4-Based E3 ubiquitin ligase1) encoded a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…OsCUL4 and OsDDB1, which are components of the CRL4‐based E3 ligase complex, have been little studied from the perspective of ubiquitination. Recently the interaction between OsDDB1 and, as a negative regulator for abiotic stress responsive protein, was confirmed (Choi et al., 2021). We isolated OsDDB1 (GenBank #AB037144), as reported previously (Bae et al., 2018; Choi et al., 2021; Ishibashi et al., 2003).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…OsCUL4 and OsDDB1, which are components of the CRL4‐based E3 ligase complex, have been little studied from the perspective of ubiquitination. Recently the interaction between OsDDB1 and, as a negative regulator for abiotic stress responsive protein, was confirmed (Choi et al., 2021). We isolated OsDDB1 (GenBank #AB037144), as reported previously (Bae et al., 2018; Choi et al., 2021; Ishibashi et al., 2003).…”
Section: Resultsmentioning
confidence: 96%
“…We therefore investigated the function of the OsDWD1 substrate receptor of the CRL4 complex and its substrates. In a recent report on rice CUL4‐based E3 ligases, OsCBE1 was a negative regulator of the abiotic stress response gene, and OsDDB1 was used to hemagglutinin (HA) tag transgenic rice plants to confirm the interaction between OsDDB1 and OsCBE1 by co‐IP (Choi et al., 2021). However, no CUL4 protein has been identified in rice to date, even though orthologs for components of the CRL4 complex in rice have been reported in annotation databases (http://rice.plantbiology.msu.edu; http://www.ncbi.nlm.nih.gov) (Marino et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tea polyphenols assist the resistance of plants to damage by external factors, such as UV-B, low temperature, and drought ( Zoratti et al, 2014 ). Genes encoding for the REF/SRPP-like protein (TEA001749), E3 ubiquitin ligase (TEA022683) and carboxylesterase (CXE) (TEA001625) were involved in plant stress resistance ( Tong et al, 2017 ; Cao et al, 2019 ; Choi et al, 2021 ). Glutathione S-transferase ( GST ) (TEA006546) was also a hub gene and involved in normal metabolism of plant secondary products, such as flavonoids and cinnamic acid ( Marrs, 1996 ).…”
Section: Resultsmentioning
confidence: 99%
“…LOC103635071 encodes an E3 ubiquitin protein ligase, which participates in a variety of physiological processes within cells by regulating the ubiquitination process of proteins, and plays an important role in regulating plant responses to abiotic stress. Choi et al [ 22 ] found that OsCBE1 encodes a novel substrate receptor for Cullin4-Based E3 ubiquitin ligase complex (C4E3), and OsCBE1 is involved in the regulation of development and abiotic stress response. Meanwhile, the mutant of OsCBE1 was insensitive to ABA during seed germination, indicating that OsCBE1 participated in the stress response through ABA signaling pathway.…”
Section: Discussionmentioning
confidence: 99%